Аналітичний огляд задач та методів побудови моделей складних систем - Тимченко, А.А.; Бойко, В.В.; Скоробрещук, В.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
In the article the analysis of the systems of the methods of identification tasks solution is made. A number of experiments based on model structural optimization are carried out. In the process of the analysis of obtained models the method of optimal complexity is found. The examined system flow diagram can be successfully for intricate analytical problems solution.